2020
DOI: 10.1101/2020.05.21.20108761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examining the bidirectional association between emotion recognition and autistic traits using observational and genetic analyses

Abstract: Background: There is mixed evidence for an association between autism spectrum disorder (ASD) and emotion recognition deficits. We sought to assess the bidirectionality of this association using phenotypic and genetic data in a large community sample. Methods: Analyses were conducted in three stages. First, we examined the bidirectional association between ASD symptoms at age 16 years and emotion recognition task (ERT) responses at age 24 years (Study 1; N=3,579); and between Diagnostic Analysis of Nonverba… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Finally, we note that including the AQ-10 scores in study 2 did not make a meaningful difference to our results, suggesting that participants' level of autistic traits did not influence our training effect. However, as this was a sample of healthy volunteers, AQ-10 scores are likely to be lower than in autistic individuals where ER difficulties have been previously reported and baseline ER accuracy is likely to be lower [11][12][13]. Thus, ERT may be more beneficial for autistic individuals, and it would be useful for future research to examine the effectiveness of ERT, in an autistic sample and other populations, that may particularly stand to benefit from improved facial ER accuracy.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Finally, we note that including the AQ-10 scores in study 2 did not make a meaningful difference to our results, suggesting that participants' level of autistic traits did not influence our training effect. However, as this was a sample of healthy volunteers, AQ-10 scores are likely to be lower than in autistic individuals where ER difficulties have been previously reported and baseline ER accuracy is likely to be lower [11][12][13]. Thus, ERT may be more beneficial for autistic individuals, and it would be useful for future research to examine the effectiveness of ERT, in an autistic sample and other populations, that may particularly stand to benefit from improved facial ER accuracy.…”
Section: Discussionmentioning
confidence: 85%
“…For example, poorer emotion recognition (ER) has been found in individuals with depression [8,9], and this may be a causal factor in the maintenance of depressive symptoms [10]. Similarly, autistic individuals or those scoring higher on autistic trait measures tend to have lower accuracy for global ER [11][12][13]. This may have implications for social development and interpersonal skills over time [14].…”
Section: Introductionmentioning
confidence: 99%
“…The struggle to recognize emotions from facial expressions is one of the earliest identifiable markers of ASD (Dawson et al, 2005). In a large sample Reed et al (2020) have found behavioral and genetic evidence for poorer emotion recognition with increasing autistic traits. In neuroimaging studies using facial emotion recognition tasks (Harms et al, 2010), individuals with ASD demonstrated altered processing (Johnson et al, 2015) in the amygdala (Dalton et al, 2005), fusiform gyri (Pierce et al, 2004;Pierce and Redcay, 2008), and posterior superior temporal gyri (Pelphrey et al, 2005).…”
Section: Introductionmentioning
confidence: 99%